'Clock-watching and box-ticking': British local authority planners, professionalism and performance targets. (7th August 2016) - Clifford, Ben
Abstract: The speed of the statutory planning system has concerned UK Governments for decades. The Labour Government of 1997–2010 placed particular emphasis on increasing the efficiency of public services through performance targets. Whilst the subsequent Coalition Government of 2010–2015 removed many targets, those measuring the speed of planning application processing were kept. These performance targets have important potential implications in terms of the autonomy and space for discretionary judgement traditionally seen as intrinsic to the professional nature of planning. Empirical material exploring how British local authority planners responded to these targets suggests they have both restricted and empowered professionals and, whilst changes to practice have occurred, professional identities have remained more resilient. This contradictory picture highlights the importance of considering the role of frontline professionals in implementing reforms.